2015
DOI: 10.1088/0741-3335/57/6/064005
|View full text |Cite
|
Sign up to set email alerts
|

Efficient propagation of ultra-intense laser beam in dense plasma

Abstract: Ultra intense laser propagation in extended, dense plasma is investigated through optical and proton probing. When a >1 kJ, 10 ps laser propagates into a long-density scale length plasma, channel formation was observed up to 0.6 n c from the analysis of optical probe images. The proton track analysis shows the formation of strong electric and magnetic fields along the plasma channel, which may lead to the observed collimated electron beam on the laser axis. These results are promising for the feasibility of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…(iii) The fast electron source might be far away from the core. Previous experiments 29,30 showed that the plasma channel created by a 10 ps high-intensity (~10 19 W cm −2 ) laser stopped in the underdense region (0.6 n c ), probably due to beam filamentation and plasma pileup in front of the channel.
Fig. 6Energy carried by fast electrons for the t LFEX = 2.6 ns case.The fraction of the LFEX energy ( η hit , blue squares, left axis) carried by fast electrons that are capable of hitting the core and laser-to-electron energy conversion efficiency ( η L→e , red dots, right axis) are plotted as a function of the divergence angle ( θ 1 ) of the T 1 -component fast electrons.
…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…(iii) The fast electron source might be far away from the core. Previous experiments 29,30 showed that the plasma channel created by a 10 ps high-intensity (~10 19 W cm −2 ) laser stopped in the underdense region (0.6 n c ), probably due to beam filamentation and plasma pileup in front of the channel.
Fig. 6Energy carried by fast electrons for the t LFEX = 2.6 ns case.The fraction of the LFEX energy ( η hit , blue squares, left axis) carried by fast electrons that are capable of hitting the core and laser-to-electron energy conversion efficiency ( η L→e , red dots, right axis) are plotted as a function of the divergence angle ( θ 1 ) of the T 1 -component fast electrons.
…”
Section: Discussionmentioning
confidence: 98%
“…(i) The laser-to-electron energy conversion efficiency ( η L→e ) might be very low (e.g., η L→e = 10% at θ 1 = 40°, dashed lines in Fig. 6), which could be a result of spending too much energy in forming the plasma channel or creating laser and electron filaments 30 , leaving little energy to produce fast electrons. (ii) The fast electrons might have a very large divergence angle (e.g., θ 1 = 75° at η L→e = 30%, dash-dotted lines in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Work carried out at Osaka University’s Institute for Laser Engineering (ILE) by Tanaka et al [ 17 ], Kodama et al [ 18 ] and Habara et al [ 19 ] suggests combining the two relativistic effects—relativistic self-focusing and relativistically induced transparency—described above to increase the penetration depth of ultra-intense laser pulses into fast ignition-relevant plasmas. These plasmas typically contain density gradients ranging from significantly underdense to relativistically critical.…”
Section: Introductionmentioning
confidence: 99%